2018
DOI: 10.1007/s12519-018-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of T-helper cell cytokine level with age in patients with biliary atresia: a preliminary study

Abstract: The serum levels of IL-1β, IL-6, IL-10 and IL-12p70 showed significant age-related differences in patients with BA. Interpretation of the role of cytokines in BA needs to take patient's age into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The pathogenesis of BA mainly includes embryonic development defects, genetic factors, environmental toxins, viral infections, abnormal in ammation and autoimmunity [8] . Most people believed that in ammatory reaction played a crucial role in the pathogenesis of BA [9] , which was manifested as persistent in ammatory reaction of the intrahepatic and extrahepatic bile ducts. In ammatory response destroyed the intrahepatic bile duct and liver structure, leading to progressive bile duct obstruction and liver brosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of BA mainly includes embryonic development defects, genetic factors, environmental toxins, viral infections, abnormal in ammation and autoimmunity [8] . Most people believed that in ammatory reaction played a crucial role in the pathogenesis of BA [9] , which was manifested as persistent in ammatory reaction of the intrahepatic and extrahepatic bile ducts. In ammatory response destroyed the intrahepatic bile duct and liver structure, leading to progressive bile duct obstruction and liver brosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the higher level of liver in ammation, the lower the decrease rate of TBIL after operation and worse prognosis. Mohanty et al [9] proposed that age has nothing to do with the expression levels of IL-6 and TGF-6 in liver tissues. Our research found that the levels of CD4 + T cells, IL-6, IL-8 and IL-33 in liver of patients aged 60 to 90 days were slightly lower than those in ≤ 60 days and ≥ 90 days groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that BA may be an immune disease mediated by T cells (7,8), and T cells and cytokines play a pivotal role in the osteogenesis of BA (9). Through the stimulation of specific antigens, the selective distribution of the T cell receptor (TCR, TR) spectrum could reflect the clonal amplification and functional changes of the Tcell population (10).…”
Section: Introductionmentioning
confidence: 99%